Factors of Students’ Perceived Satisfaction with Distance Learning during the Covid-19 Pandemic - Zuković, Slađana; Stojadinović, Dušica; Slijepčević, Senka (Društvene i humanističke studije (Online), 2023)
Bearing in mind the specifics of the educational process in the online context and the factors of satisfaction with this type of teaching in a crisis, the paper presents the results of research aimed at examining student satisfaction with distance learning in the conditions of the coronavirus pandemic. The research was conducted on a convenient sample of 505 students in the second cycle of primary school education in the Republic of Serbia. A modified version of the Technology Acceptance Model (Davis 1989) instrument was used for the research. Using factor analysis, we identified two subscales (Attitudes towards distance learning and Motivated behaviour) for which we established criterion validity. The obtained results for the entire scale showed that the respondents moderately positively assessed the factors of satisfaction with distance learning, while female students and respondents from two-parent families rated satisfaction with this aspect at a higher level. The analysis of the differences in the answers obtained concerning the measured socio-demographic variables showed that the answers on the subscale Attitudes towards distance education of the child differ concerning the birth order in the family. On the subscale Motivated behaviour differences were determined concerning gender, school achievement and family structure. In addition to the research limitations highlighted in the paper, the results generally suggest that strengthening the sense of personal control and self-regulation is one of the more essential ways to improve satisfaction, motivation and intention to learn during distance learning.